Oh, Help Me in My Weakness : Entreaties and the Dissolution of Communal Time in John Wesley Harding - Reginio, Robert (Aktualitet - Litteratur, kultur og medier, 2023)
Using Walter Benjamin’s analysis of storytelling as a conceptual frame and referring to his ethical adherence to what Max Pensky termed Benjamin’s “melancholy dialectics,” this essay offers a thoroughgoing reading of Bob Dylan’s song “Drifter’s Escape” in order to examine the careful parsing of modes of public address and power Dylan undertakes in the song, and to argue that John Wesley Harding, as a song series, critiques dominant modes of American history telling. There has been a recent turn in Dylan Studies towards considering the songs as interventions in (or even works of) history. Taking this background as an essential turn in the field, especially considering the work the Bob Dylan Archive may enable, this essay argues that it is in temporal indeterminacy that Dylan’s work becomes a powerful expression of the vexations of history and memory in America. By “temporal indeterminacy” I mean to indicate a sense of the present shaped by an overflow of unprocessed (essentially silenced) memories and an almost pathological desire for the closure offered by dreams of historical redemption. Thereby the essay argues that the songs on John Wesley Harding are interventions in the typical modes of American storytelling rather than works of history themselves.